2018
DOI: 10.1016/j.fertnstert.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Shorter leukocyte telomere length is associated with risk of nonobstructive azoospermia

Abstract: This is the first report that short LTL is associated with NOA, shedding light on an important biological pathway involved in the etiology of this form of male factor infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…Similarly, longer leukocyte TL in 10 fertile men than in 10 oligozoospermic patients was reported by Amirzadegan et al 25 . On the other hand, Yang et al 37 . reported shorter leukocyte TL in 349 non‐obstructive azoospermia patients than in 247 obstructive azoospermia patients and 270 normospermic men, and results from the Tahamtan et al 30 .…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Similarly, longer leukocyte TL in 10 fertile men than in 10 oligozoospermic patients was reported by Amirzadegan et al 25 . On the other hand, Yang et al 37 . reported shorter leukocyte TL in 349 non‐obstructive azoospermia patients than in 247 obstructive azoospermia patients and 270 normospermic men, and results from the Tahamtan et al 30 .…”
Section: Resultsmentioning
confidence: 58%
“…Regarding TL in leukocytes, three studies reported lower leukocyte TL in infertile patients than in fertile men. 24,28,36 Similarly, longer leukocyte TL in 10 fertile men than in 10 oligozoospermic patients was reported by Amirzadegan et al 25 On the other hand, Yang et al 37 reported shorter leukocyte TL in 349 nonobstructive azoospermia patients than in 247 obstructive azoospermia patients and 270 normospermic men, and results from the Tahamtan et al 30 study showed significantly lower leukocyte TL in men with infertility resulting from varicocoele than fertile controls. Only two studies found no differences in leukocyte TL between normozoospermic and oligozoospermic men 14 or between fertile and infertile subjects.…”
Section: Differences In Leukocyte Tl Between Fertile and Infertile Or...mentioning
confidence: 67%
“…Moreover, samples that were used for IVF and had abnormal STLs did not produce a successful pregnancy, whereas samples that had STLs within the normal range had a 35.7% success rate (79). Likewise, males with azoospermia exhibited a shortened STL (69,70), as well as a shorter LTL (85,86).…”
Section: Telomere Length and Male Infertilitymentioning
confidence: 98%
“…A positive association between male infertility factors and TL was observed in 19 studies (68-86) and a negative association in 2 studies (39,87) (Table II). In total, 15 of the positively associated studies detected a sperm TL (STL) association (68-70,72,74-84), while 3 studies detected an LTL association (73,85,86), and one study detected both STL and LTL (71). In several studies, shorter STL was reported in association to infertility (72,76,78,80) while Vecoli et al reported an increase in STL in areas of high environmental exposure (77).…”
Section: Telomere Length and Male Infertilitymentioning
confidence: 99%
“…Liu et al found that fertilization of telomerase-de cient spermatozoa with wild-type oocytes resulted in decreased fertilization and blastocyst formation rates, increased embryo fragmentation, and increased cell apoptosis [43]. However, there're also some studies didn't con rm this result [45],[46],[48], [49]. A meta-analysis involving 60 samples found that there was a weak correlation between sperm telomere length (STL) variation and lower fertilization rate [rho-Spearman coe cient is -0.04(95% CI, -0.203-0.113; p = 0.57)] [45].…”
Section: Discussionmentioning
confidence: 99%